Isothermal Multiple Displacement Amplification : A Highly Reliable Approach for Generating Unlimited High Molecular Weight Genomic DNA from Clinical Specimens - Luthra, Rajyalakshmi (American Society for Investigative Pathology, 2004)
Isothermal multiple strand displacement amplification (IMDA) of the whole human genome is a promising method for procuring abundant DNA from valuable and often limited clinical specimens. However, whether DNA generated by this method is of high quality and a faithful replication of the DNA in the original specimen, allowing for subsequent molecular diagnostic testing, requires verification. In this study, we evaluated the suitability of IMDA-generated DNA (IMDA-DNA) for detecting antigen receptor gene rearrangements, chromosomal translocations, and gene mutations using Southern blot analysis, polymerase chain reaction (PCR) methods, or sequencing methods in 28 lymphoma and leukemia clinical specimens. Molecular testing before and after whole genome amplification of these specimens using the IMDA technique showed concordance in 27 of 28 (96%) specimens. Analysis of IMDA-DNA by Southern blot analysis detected restriction fragments >12 kilobases long. No amplification bias was observed at all loci tested demonstrating that this method can be useful in generating large amounts of unbiased, high molecular weight DNA from limited clinical specimens.